Correction: Molecular Determinants of Agonist Selectivity in Glutamate-Gated Chloride Channels Which Likely Explain the Agonist Selectivity of the Vertebrate Glycine and GABAA-ρ Receptors - The PLOS ONE Staff (PLOS ONE, 2014)
null